Are Toll-Like Receptors and Decoy Receptors Involved in the Immunopathogenesis of Systemic Lupus Erythematosus and Lupus-Like Syndromes? - Giuliana Guggino; Anna Rita Giardina; Francesco Ciccia; Giovanni Triolo; Francesco Dieli; Guido Sireci (Clinical and Developmental Immunology)
In this paper we focus our attention on the role of two families of receptors, Toll-like receptors (TLR) and decoy receptors (DcR) involved in the generation of systemic lupus erythematosus (SLE) and lupus-like syndromes in human and mouse models. To date, these molecules were described in several autoimmune disorders such as rheumatoid arthritis, antiphospholipids syndrome, bowel inflammation, and SLE. Here, we summarize the findings of recent investigations on TLR and DcR and their role in the immunopathogenesis of the SLE.